Women's stated preferences for conditional cash transfer programs focused on maternal and child health and nutrition in India (P22-012-19) - Kachwaha, Shivani; Rao, Krishna; Kaplan, Avril; Bishai, David (Oxford University Press, 2019)
Conditional Cash Transfers (CCTs) are important national strategies to improve maternal and child health and nutrition. India recently began implementing a Maternity Benefit Program (MBP) to encourage health care use during pregnancy and early childhood; under discussion is to include child nutrition services within a CCT program. This paper aims to understand the preferences of mothers with young children for design features (cash transfer amount and conditionalities) of CCT programs.